Privacy invasion strategy in media interview - A. V. Zhupinskaya (Вестник Самарского университета: История, педагогика, филология)
Nowadays questions of privacy violation and its protection gradually spreads from the problem belonging to the field of sociology and psychology to the major interest of linguistic researches, first of all it concerns theory of communication, pragmatic linguistics and dialogue studies. This article is devoted to the study of initiating communicative strategy of interlocutor’s privacy invasion (strategy of personal borders violation) which is investigated on the basis of English and Russian media interviews, due to the wide representation and variability in realization of the specified strategy in this particular genre of media discourse. In media discourse and in interview as one of its central genres two tendencies are widespread: the tendency to frankness within the concept of “new sincerity” and the tendency to conflict and provocative behavior. It generates a large number of inconvenient private questions. In this article, a set of tactics included in the strategy of privacy invasion is described with the help of contextual analysis. Three types of invasion tactics are distinguished: preparing tactics, tactics of direct invasion and tactics of insisting on the answer on the basis of such parameters as a position in dialogue (initiating and reactional) and the contribution to the achievement of communicative aim (main and additional). Illocutionary characteristics (form of interrogation, suggestion, request and representation) and typical means of verbalization are established for each type of the mentioned tactics. Various degree of representation in dialogue of the specified tactics allows to single out two main types of privacy invasion: marked and unmarked.